Satisfaction with clinical practice, competences and education in nursing at Slovak universities [SPOKOJNOSŤ S KLINICKOU PRAXOU, KOMPETENCIAMI A VZDELÁVANÍM V OŠETROVATEĽSTVE NA SLOVENSKÝCH UNVERZITÁCH] - Nemcová, Jana; Hlinková, Edita; Ovšonková, Anna; Derňarová, Ľubica; Botíková, Andrea; Poliaková, Nikoleta; Kadučáková, Helena; Slamková, Alica; Jankechová, Monika; Visiers-Jiménez, Laura; Kajander-Unkuri, Satu (Faculty of Healthcare, Alexander Dubcek University of Trencin, 2025)
Introduction: Clinical practice, for graduating students in nursing education, deserves attention in relation to competences, as well as for deciding whether to stay in the profession.
Objectives: To determine students' perception of the clinical environment, self-assessment of competences and satisfaction with nursing education before completing their studies at Slovak universities.
Methodology: The cross-sectional research design was part of the larger European project Competence of nursing students in Europe, under the auspices of Turku University in Finland. Consent to publish national results was obtained by signing a contract with participation in an international project. Students participated in filling out The Clinical Learning Environment (CLES) and Supervision and The Nurse Competence Scale (NCS) questionnaires online. For the statistical processing of the results, we used descriptive and inductive statistics, where P < 0.05, Pearson's correlation coefficients and confidence intervals (Confidence Interval, CI).
Results and discussion: The total CLES score was 5.4 (SD ± 2.0). The most positive rating was the environment of the clinical workplace 6.0 (SD ± 2.2); the lowest rated was the student's relationship with the mentor 5.1 (SD ± 2.7). The relationship between ratings of the clinical learning environment and student competencies was statistically significant and positive (r= 0.41; P < 0.0001), as were the correlations for each NCS category and each CLES subdimension. The strongest correlations were between the helping role and the pedagogical atmosphere (r = 0.44; P < 0.0001) and the helping role and the relationship with the mentor (r = 0.40; P < 0.0001). Nursing students with a very good level of competence had a more positive perception of the clinical learning environment.
Conclusion: High-quality practice and education support the development of nursing competencies, the provision of safe care and are also motivation for staying in the nursing profession.